Mở rộng cấu trúc và hàm Liapunov cho mạng nơ ron Hopfield - Hoan, Nguyễn Quang (Journal of Computer Science and Cybernetics, 2016)
The existence the Hopfield neural network and the Liapunov function guarantees the convergence to some local minimum of these network with linear inputs [1,6]. But standard Hopfield architecture [3, 14] is limited in its capacity of linear classifiers with higher performances. We also regarded some assumptions on these architectures and the their stability.